Beyond Exception : New Interpretations of the Arabian Peninsula - Kanna, Ahmed; Vora, Neha, 1974-; Le Renard, Amelie (Book collections on Project MUSE., 2020)
"This book analyzes what the theory of exceptionalism in the Arabian Peninsula does, how it is used by various people, and how it helps shape power relations in the societies that the authors study"--